Effect of the metalloproteinase inhibitor batimastat in the systemic toxicity induced by Bothrops asper snake venom: understanding the role of metalloproteinases in envenomation - Rucavado Romero, Alexandra (2014)
The peptidomimetic hydroxamate metalloproteinase inhibitor batimastat (BB-94) was assessed for its ability to neutralize the systemic effects (lethality, hemorrhage and coagulopathy) induced by the venom of Bothrops asper, the most important snake from a medical standpoint in Central America. Batimastat inhibited lethality when a venom challenge dose of two LD50s was used by intraperitoneal and intravenous routes, with ED50s of 250 and 22 μM, respectively. With a challenge dose of three LD50s, lethality was not abrogated, but a conspicuous and dose-dependent delay in the time of death was observed in mice injected with mixtures of venom plus batimastat. Upon incubation with 500 μM batimastat, venom LD50 increased 2.86-fold (intraperitoneal route) and 2.37-fold (intravenous route), when compared with LD50 of venom alone. Batimastat also inhibited the hemorrhagic effect induced by venom in the lungs after intravenous injection. Moreover, batimastat exerted a significant inhibition of in vitro coagulant and in vivo defibrinogenating effects of venom, evidencing that metalloproteinases play a key role in the coagulopathy characteristic of B. asper envenomation. The remaining uninhibited coagulant effect is due to serine proteinases, i.e. thrombin-like enzymes, since this effect was completely abrogated by the combination of batimastat and PMSF. Our results stress the view that metalloproteinases play a relevant role in the systemic pathophysiology of B. asper envenomation and that metalloproteinase inhibitors may become a therapeutic alternative in this pathology.